2014
DOI: 10.1038/nphys2935
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of charge density wave domain walls above the superconducting dome in 1T-TiSe2

Abstract: Superconductivity (SC) in so-called "unconventional superconductors" is nearly always found in the vicinity of another ordered state, such as antiferromagnetism, charge density wave (CDW), or stripe order. This suggests a fundamental connection between SC and fluctuations in some other order parameter. To better understand this connection, we used high-pressure x-ray scattering to directly study the CDW order in the layered dichalcogenide TiSe 2 , which was previously shown to exhibit SC when the CDW is suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
217
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(238 citation statements)
references
References 29 publications
(48 reference statements)
17
217
1
3
Order By: Relevance
“…Going beyond the reported critical pressure of 5.1 GPa (Ref. [5]), we find a still slightly enhanced 0.3 at 6.3 GPa, which is further reduced to the ambient pressure value of around 0.1 at 9.6 GPa [ Fig. 5(e)].…”
Section: Tise 2 Under Pressurementioning
confidence: 67%
See 1 more Smart Citation
“…Going beyond the reported critical pressure of 5.1 GPa (Ref. [5]), we find a still slightly enhanced 0.3 at 6.3 GPa, which is further reduced to the ambient pressure value of around 0.1 at 9.6 GPa [ Fig. 5(e)].…”
Section: Tise 2 Under Pressurementioning
confidence: 67%
“…X-ray diffraction [5] revealed that the superconducting phase under pressure is completely surrounded by the CDW ordered phase rather than being centered on the critical pressure [4]. In this work we use inelastic x-ray scattering to investigate the superconducting pairing mechanisms in Cu X TiSe 2 and 1T-TiSe 2 under pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, as already proposed in high-pressure [16] and carrier injection [17] experiments, superconductivity may arise from the inhomogeneities of the CDW pattern. Moreover, spectroscopy shows Cu intercalation to shift the chemical potential to higher energies and increase the LDOS at the Fermi level providing a favorable electronic configuration for the appearance of superconductivity above x ¼ 0.04.…”
mentioning
confidence: 96%
“…These domains are predominantly surrounded by Cu-rich regions, and tend to be π-phase shifted with a few atomically sharp boundaries separating adjacent domains. Each domain is locally commensurate, and the slight incommensurability reported in some bulk experiments [16,17] might result from the stacking along the c axis of such phase-shifted domains. A similar break up of the CDW into phase-shifted domains has been reported recently in Ti intercalated crystals [21] where the effect is observed already for 2% Ti content.…”
mentioning
confidence: 99%
See 1 more Smart Citation